Politeness Maxims as A Positive and Negative Speech Act by The Characters “Habibie & Ainun” (2012) - Irma Nuraeni Salsabila; Vika Fransica (Journal of Social Science, 2022)
A language is a tool for communicating in social life between individuals. Language makes people interact with each other. While the maxims is an important aspect of language so that the delivery and acceptance run well without causing problems in the future. This research uses a qualitative approach method with the analysis method, to conduct an in-depth analysis related to the findings of data from the film "Habibie & Ainun". Data retrieval is carried out by researchers with purposive sampling techniques where the selection of data and its use is only following the purpose of the study. The results showed that in the film "Habibie & Ainun" the characters more often use positive speech following existing norms and cultures.